Growing old with and via media - Iversen, Sara Mosberg; Blaakilde, Anne Leonora; Wilińska, Monika; Sandvik, Kjetil (MedieKultur: Journal of media and communication research, 2017)
What we understand at any given time as “old age” may seem to have a very straightforward and factual base. Yet, in the words of Simone de Beauvoir, “as far as our own species is concerned old age is by no means easy to define” (de Beauvoir, 1996, p. 9). Even the most positivist sciences have to admit that old age is a “a heterogeneous event that some individuals tolerate better than others” (Balcombe & Sinclair, 2001, p. 845). That is, “old age” as a biological and physiological phenomenon has many and variable causes that may become visible at differing points in individual lives. Moreover, the phenomenon of ageing cannot be explained by any one universal theory (Balcombe & Sinclair, 2001, pp. 845-846). What it means to be old in a particular society at any given time is, thus, a matter of social and cultural construction that may vary greatly from place to place and at different historical times (Hazan, 1994).